Synthesis, characterisation and cytotoxicity of gold microwires for ultra-sensitive biosensor development - Nurul Akmal, Che Lah; Gray, Robert; Trigueros, Sonia (BioMed Central Ltd, 2021)
With the long-term goal of developing an ultra-sensitive microcantilever-based biosensor for versatile biomarker detection, new controlled bioreceptor-analytes systems are being explored to overcome the disadvantages of conventional ones. Gold (Au) microwires have been used as a probe to overcome the tolerance problem that occurs in response to changes in environmental conditions. However, the cytotoxicity of Au microwires is still unclear. Here, we examined the cytotoxicity of Au microwires systems using both commercial and as-synthesised Au microwires. In vitro experiments show that commercial Au microwires with an average quoted length of 5.6 µm are highly toxic against Gram-negative Escherichia coli (E. coli) at 50 µg/mL. However, this toxicity is due to the presence of CTAB surfactant not by the microwires. Conversely, the as-synthesised Au microwires show non-cytotoxicity even at the maximum viable concentration (330 µg/mL). These findings may lead to the development of potentially life-saving cytotoxicity-free biosensors for an early diagnostic of potential diseases.